2017
DOI: 10.5812/jjhs.14329
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure of Train Drivers to Static and Extremely Low Frequency Magnetic Fields in Tehran Subway

Abstract: Background: Electrification of transport systems currently deserves top priority in Iran. Such systems generate a magnetic field in static or extremely low frequency ranges. Therefore, train drivers may be exposed to these fields occupationally. Objectives: The current study aimed to measure the intensity of static magnetic field (SMF) and extremely low frequency magnetic fields (ELF-MF) in the subway trains of Tehran City in different train types and situations to show drivers' exposure to SMF and ELF-MF. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…The results of these studies showed comparatively high exposure from civil communication bands and the major source of exposure in the subway was GSM900. Most previous studies focused on the coverage of the wireless system in subways or a high-speed railway environment [24], and little information has been published on electromagnetic exposure safety in the rail transit system, except for recent studies [8,25,26]. The research on the general public electromagnetic exposure of subway passengers, especially children, is limited.…”
Section: Introductionmentioning
confidence: 99%
“…The results of these studies showed comparatively high exposure from civil communication bands and the major source of exposure in the subway was GSM900. Most previous studies focused on the coverage of the wireless system in subways or a high-speed railway environment [24], and little information has been published on electromagnetic exposure safety in the rail transit system, except for recent studies [8,25,26]. The research on the general public electromagnetic exposure of subway passengers, especially children, is limited.…”
Section: Introductionmentioning
confidence: 99%